A gravo-aeroelastically scaled wind turbine rotor at field-prototype scale with strict structural requirements. (August 2020) - Yao, Shulong; Griffith, D. Todd; Chetan, Mayank; Bay, Christopher J.; Damiani, Rick; Kaminski, Meghan; Loth, Eric
Abstract: A new sub-scale field-prototype design solution is developed to realize the dynamics, structural response, and distributed loads (gravitational, aerodynamic, centrifugal) that are characteristic of a full-scale large, modern wind turbine rotor. Prior work in sub-scale wind turbine testing has focused on matching aerodynamic/aero-elastic characteristics of full-scale rotors at wind tunnel scale. However, large-scale rotor designs must expand beyond this limited set of scaling parameters for cost-effective prototyping and meet strict requirements for structural safety for field testing. The challenge lies in producing a structural design meeting two competing objectives: novel scaling objectives that prescribe the sub-scale blade to have low mass and stiffness; and traditional structural safety objectives that drive the design to have higher stiffness and mass. A 20% gravo-aeroelastically scaled wind turbine blade is developed successfully that satisfies these competing objectives. First, it achieved close agreement for non-dimensional tip deflection and flap-wise blade frequency (both within 2.1%) with a blade mass distribution constrained to produce target gravitational and centrifugal loads. Second, the entire blade structure was optimized to ensure a safe, manufacturable solution meeting strict strength requirements for a testing site that can experience up to 45 m / s wind gusts. The prototype-scale blade was fabricated and successfully proof-load tested. Highlights: A 20% gravo-aeroelastically scaled rotor to replicate a full-scale 13.2 MW rotor. Design solution meets scaling targets within 2.1% for deflection/frequency. Design solution also satisfies strict structural load safety requirements. Prototype-scale blade was successfully proof load tested prior to field testing. First-ever prototype meeting gravo-aeroelastic scaling and loads requirements.